Analysis of Online Learning Understanding Patterns at Budi Darma University Using the C5.0 Algorithm - Firman Telaumbanua; Johanes Mario Purba; Dito Putro Utomo (The IJICS (International Journal of Informatics and Computer Science), 2021)
Online learning is a learning process that is carried out without face to face, but at a distance that utilizes communication and information technology that utilizes the internet. The emergence of the online learning process provides considerable benefits, both for the manager of the information system and for students and students. Currently, the development of online learning is becoming popular among schools and universities. This is caused by the corona virus or what is often called Covid-19. Covid-19 is one of the viruses that first emerged and developed in China, especially in the city of Wuhan. Initially this virus only infects a few people, but in fact this virus can move places or can be transmitted through direct contact with the sufferer. This virus has infected the whole world so this is an international problem that must be addressed. Various efforts have been made, one of which is in the field of education. The closure of schools and colleges is an effort made to break the chain of development of COVID-19, so that the teaching and learning process is carried out online. In this study, an analysis of student satisfaction assessment will be carried out on the online learning process using the existing methods in data mining. Data mining has several algorithms that are used to solve these problems, one of which is the C5.0 algorithm. The result of this study is to find out the results of the satisfaction assessment of online learning during the Covid-19 pandemic